Non-invasive ultrasonic tomography: liquid/gas flow visualization - Abdul Rahim, Ruzairi; Fazalul Rahiman, M. H.; Mohd. Taib, M. N. (2005)
This paper presents the non-invasive ultrasonic tomography system for imaging liquid and gas flow. Transmission-mode approach has been used for sensing the liquid/gas two-phase flow, which is a kind of strongly inhomogeneous medium. The algorithms used to reconstruct the concentration profile for two-phase flow using fan-shaped beam scanning geometry were presented. Experiments showed that the performance of the system is acceptable. Results of the experiments using LBPA, HRA and HBRA were discussed.